Introduction of New Preparations for Gene Diagnostics of Dengue Fever and Cholera - E. V. Naidenova; N. A. Osina; V. E. Kouklev; Yu. I. Yashechkin; T. V. Bugorkova; I. V. Shul’Gina; O. A. Lobovikova; S. A. Shcherbakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2012)
Presented is the information on technical and medical trials of new generation preparations for gene diagnostics of Dengue fever and cholera, based on the multiple factor analysis. Application of these preparations makes it possible not only to detect pathogen but also to carry out its expedited identification in accordance with epidemiological significance and taxonomic status.